ONLINE SHOPPING AND FOLKLORE - A REVIEW: WITH SPECIAL REFERENCE TO INDIA - Vyas, Anand; Gupta, Sachin (International Journal of Research -GRANTHAALAYAH, 2014)
The purpose of this research paper is to classify factors affecting the online shopping in India. The weighty growth of online shopping is noticeable in India. More and more consumer is transferring to online shopping rather than traditional buying methods. Many myths and misconceptions emerge in India regarding online shopping. Every new thing, when it is not cleared by all the people properly, it is only a nightmare. Online shopping is intricate in nature. As we know the number of online transactions have been increased, but it is still under the dark room. Government and E-commerce companies should take necessary steps for reducing the level of misconceptions and myths of online shopping in India. This research paper’s purpose is to identifying ‘How’ the companies can be able to overcome these fake information regarding online shopping. Also improve company’s sales figure, for the upliftment of company as well as an Indian economy.